Structural Transformation in South Africa The Challenges of Inclusive Industrial Development in a Middle-Income Country - Andreoni, Antonio; Mondliwa, Pamela; Roberts, Simon; TREGENNA, FIONA (Oxford University Press, 2021)
Taking South Africa as an important case study of the challenges of structural transformation, the book offers a new micro-meso level framework and evidence linking country-specific and global dynamics of change, with a focus on the current challenges and opportunities faced by middle-income countries. Detailed analyses of industry groupings and interests in South Africa reveal the complex set of interlocking country-specific factors which have hampered structural transformation over several decades, but also the emerging productive areas and opportunities for structural change. The structural transformation trajectory of South Africa presents a unique country case, given its industrial structure, concentration, and highly internationalized economy, as well as the objective of black economic empowerment. The book links these micro-meso dynamics to the global forces driving economic, institutional, and social change. These include digital industrialization, global value-chain consolidation, financialization, and environmental and other sustainability challenges which are reshaping structural transformation dynamics across middle-income countries like South Africa. While these new drivers of change are disrupting existing industries and interests in some areas, in others they are reinforcing existing trends and configurations of power. The book analyses the ways in which both the domestic and global drivers of structural transformation shape-and, in some cases, are shaped by-a country's political settlement and its evolution. By focusing on the political economy of structural transformation, the book disentangles the specific dynamics underlying the South African experience of the middle-income country conundrum. In so doing, it brings to light the broader challenges faced by similar countries in achieving structural transformation via industrial policies.